2023
DOI: 10.3390/v15030717
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Severity of SARS-CoV-2 Infection Compared to Respiratory Syncytial Virus and Other Viral Respiratory Infections in Children Less than Two Years of Age

Abstract: The spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the implementation of restrictive measures led to a dramatic reduction in respiratory syncytial virus (RSV) occurrence together with rare and mild bronchiolitis induced by SARS-CoV-2. We described the respiratory picture of SARS-CoV-2 infection and evaluated the frequency and the severity of SARS-CoV-2 bronchiolitis comparing it with other respiratory viral infections in children less than two years of age. The severity of respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In this study, more RSV‐disease was seen in hospitalized children compared with SARS‐CoV‐2 and influenza. In contrast, several other studies reported that the prevalence of RSV disease decreased dramatically after the emergence of SARS‐CoV‐2 20–22 . A study in the United States found that RSV circulation was historically low during 2020–2021, began earlier and continued longer during 2021–2022 compared with prepandemic years and seasons 23 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this study, more RSV‐disease was seen in hospitalized children compared with SARS‐CoV‐2 and influenza. In contrast, several other studies reported that the prevalence of RSV disease decreased dramatically after the emergence of SARS‐CoV‐2 20–22 . A study in the United States found that RSV circulation was historically low during 2020–2021, began earlier and continued longer during 2021–2022 compared with prepandemic years and seasons 23 .…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, several other studies reported that the prevalence of RSV disease decreased dramatically after the emergence of SARS‐CoV‐2. 20 , 21 , 22 A study in the United States found that RSV circulation was historically low during 2020–2021, began earlier and continued longer during 2021–2022 compared with prepandemic years and seasons. 23 In China RSV disease showed atypical seasonality during the pandemic, with a peak incidence in May 2020 and a second peak in November 2020, which was different from the typical winter peak observed in previous years.…”
Section: Discussionmentioning
confidence: 99%
“…Seven types of seasonal respiratory viruses were identified in mixed infections with SARS-CoV-2, among which RSV was the most common co-pathogen. A study conducted in Italy between 2021 and 2022 also reported a high prevalence of RSV coinfection with SARS-CoV-2 in children [ 38 ]. Similarly, a 2020–2021 study in Ecuador found RSV to be the second most common co-pathogen after influenza A [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the milder clinical course of SARS-CoV-2 infection observed in children in comparison to adults, cases of a delayed hyperinflammatory condition, known as Multisystem Inflammatory Syndrome in children (MIS-C), occurring 2-6 weeks after acute SARS-CoV-2 infection, have been described [1][2][3][4][5]. This syndrome is characterized by persisted fever and multiorgan dysfunction, which are accompanied by laboratory evidence of inflammation [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%